The Deoptimization of Rabies Virus Matrix Protein Impacts Viral Transcription and Replication - Luo, Jun (Viruses, 2019)
Rabies virus (RABV) matrix (M) protein plays several important roles during RABV infection. Although previous studies have assessed the functions of M through gene rearrangements, this interferes with the position of other viral proteins. In this study, we attenuated M expression through deoptimizing its codon usage based on codon pair bias in RABV. This strategy more objectively clarifies the role of M during virus infection. Codon-deoptimized M inhibited RABV replication during the early stages of infection, but enhanced viral titers at later stages. Codon-deoptimized M also inhibited genome synthesis at early stage of infection and increased the RABV transcription rates. Attenuated M through codon deoptimization enhanced RABV glycoprotein expression following RABV infection in neuronal cells, but had no influence on the cell-to-cell spread of RABV. In addition, codon-deoptimized M virus induced higher levels of apoptosis compared to the parental RABV. These results indicate that codon-deoptimized M increases glycoprotein expression, providing a foundation for further investigation of the role of M during RABV infection.